Sexing as a tool for reinsertion of Amazona aestiva parrots to nature: use of less invasive technique (Research, Society and Development, 2021)
The sexing birds is considered an important tool for behavioral studies and programs for the reintroduction of animals into the wild. Several techniques are used for this purpose, such as laparoscopy, magnetic resonance and molecular sexing. The first are considered more invasive and stressful for the animal, and the last is considered the most accurate. According to it, the aim of this study was to compare the effectiveness of using three sets of primers in the molecular sexing process of true parrots (Amazona aestiva). Blood samples from 10 animals were collected at a Wildlife Screening Center (CETAS) in Bahia, Brazil. The DNA was extracted and the molecular markers amplified by Polymerase Chain Reaction (PCR) using primer pairs P2/P8, 1237L/1272H and 2250F/2718R. The amplified material was visualized with electrophoresis performed at 2% agarose and 12.5% polyacrylamide gels. Among the primer sets used, the 2250F/2718R pair showed the best results for the sexing process, including visualization of the amplified products on an agarose gel. Agarose gel electrophoresis is considered to be faster and cheaper. The results revealed a sample composition of 5 males (0.5) and 5 females (0.5).